Green-Synthesized Carbon Quantum Dots from Banana Peel Waste for Sustainable Label-Free Fluorescent Biosensing of Prostate Cancer Biomarker - Nor Pana Yupa; Dian Putri Mustika (Science Journal Get Press, 2026)
A novel fluorescent biosensing platform for the label-free, sustainable detection of prostate-specific antigen (PSA) was developed using green-synthesized carbon quantum dots (CQDs) derived from banana peel (Musa acuminata) agricultural waste. CQDs were fabricated via a one-step hydrothermal carbonization at 200°C for 8 hours, yielding quasi-spherical nanoparticles with an average diameter of 3.2 ± 0.5 nm, a quantum yield of 18.4%, and characteristic blue emission at 460 nm (λex = 360 nm). Rich surface functionalization with hydroxyl (–OH), carboxyl (–COOH), and amino (–NH₂) groups enabled covalent conjugation of a PSA-specific aptamer via EDC/NHS coupling chemistry. The resulting CQD-aptamer biosensor exhibited a broad linear detection range of 0.01–50 ng/mL with an ultralow limit of detection (LOD) of 0.008 ng/mL (S/N = 3), well within the clinical diagnostic threshold of 4 ng/mL for PSA monitoring. Selectivity studies demonstrated negligible cross-reactivity (<3.5%) against common serum interferents including CEA, AFP, albumin, and glucose. Spike-and-recovery experiments in diluted human serum yielded recovery values of 96.8–103.2% with RSDs below 2.5%, confirming robust performance in complex biological matrices. Estimated material costs (~$0.12/mg CQD) and the waste-valorization approach align with green chemistry principles and circular economy objectives. This work establishes banana peel-derived CQDs as cost-effective, eco-friendly, and analytically competitive nanoprobes for point-of-care cancer biomarker detection.